Evaluation of the Rationality of Hypertension Treatment in Indonesia Based on JNC 7 and JNC 8 Treatment Standards: A Review - Pratama Immanuel Parlinggoman Sagala; Atika Atika; Jef Gishard Kristo Kalalo (Jurnal Pijar MIPA, 2026)
Hypertension is a multifactorial chronic disease and a leading cause of global morbidity and mortality, with a high prevalence in Indonesia. Irrational pharmacotherapy can reduce therapeutic effectiveness, increase the risk of adverse drug reactions, and exacerbate the economic burden on the healthcare system. This study aims to evaluate the rationality of hypertension treatment in Indonesia based on the Joint National Committee 7 (JNC 7) and 8 (JNC 8) therapy standards. A literature review was conducted on research articles accessed via Google Scholar, published between 2015 and 2025. Of the 675 identified articles, 10 met the inclusion criteria, which required that the articles contain percentage data on the rationality of hypertension treatment and use JNC 7 or JNC 8 as a reference. The results indicate that the appropriate indication aspect achieved the highest level of adherence, with 8 out of 10 studies (80%) reporting 100% compliance. The aspect of appropriate dosage was also high, exceeding 97% in 9 studies (90%). However, the appropriate drug selection rate showed wide variation, ranging from 48.65% to 100%. This inconsistency was primarily attributed to the prevalent use of monotherapy in stage 2 hypertension patients, for whom combination therapy is recommended. Calcium Channel Blockers (CCBs), particularly amlodipine, were the most frequently prescribed antihypertensive class, dominating the prescribing patterns in 8 out of the 10 studies (80%). In conclusion, hypertension treatment in Indonesia demonstrates a high degree of rationality concerning indication, drug selection, and dosage appropriateness, aligning with JNC standards to achieve optimal blood pressure control.